Penerapan Manajemen Operasional pada Usaha Pencetakan (Sudi Kasus CV. Ekribafam Multi Karya, Kota Serang BANTEN) - Annisa Nurfadilla; Nur Alam; Rifa’i Rifa’i; Simun Simun (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
This research was conducted at the printing company CV. Ekribafam Multi Karya, Serang City, Banten. This study aims to find out how important the implementation of operational management is in a business in order to see how effective the products produced by the printing company CV. Ekribafam Multi Karya are. This research was conducted using a qualitative approach. Where qualitative research is data in the form of words or statements. This study aims to analyze the influence of operational management on the printing company CV. Eribafam Multi Karya. Data collection in this study was carried out by means of interviews, observations, and literature reviews. So that it produces conclusions.